A qualitative study of resiliency of tsunami survivors in Aceh, Indonesia - Zaini, Mimi Fitriana (Kulliyyah of Education, International Islamic University Malaysia, 2017)
The current research sought to explore the lived experience of tsunami survivors in Aceh towards the devastating impacts. The study investigated on how their experience was gradually transformed into recovery and resiliency from their own perspectives. The study also investigated coping strategies from internal and external components of the survivors in increasing their strengths and posttraumatic growth. An in-depth and semi structure interview was conducted to seven survivors. The selection of the informants was based on a purposive sampling procedure. Data collection was gained from in-depth interview and observation with document analysis of the field notes, audio tapes, and interview transcriptions. The research exposed four main findings; 1) Survivors developed coping strategies from their own capacities to enhance their resilience. It was found that their psychological components, comprising of self-efficacy, self-esteem, self-regulation and internal locus of control were the internal components to improve strengths living with adversity. 2) Survivors also developed their coping mechanisms from their religion, social norms and values as well as from other people in their surroundings. It was found that their psychosocial components, comprising of religion, culture, family and community were their external elements to uplift strengths living with adversity. 3) Survivors developed their learning capacity to recover from devastating trauma. It was found that the way they learned from their surroundings was their process of recovery to develop coping skills. It was also found that they learned from the devastating event to increase strengths to have a transformation of the new life. 4) Survivors increased their strengths to enhance resiliency from the influential aspects of education, transferred by the social agencies. It was found that family and community re-instilled religious values and social norms and transferred significant knowledge to the survivors to be resilient. The research concluded that survivors developed life coping mechanisms to deplete devastating trauma and transformed their lives through two general methods; 1) Personal enrichment and 2) Family and Community empowerment methods.